2007
DOI: 10.1038/sj.ijo.0803651
|View full text |Cite
|
Sign up to set email alerts
|

School-based physical activity and changes in adiposity

Abstract: Objective: School-based physical education (PE) is often proposed as a strategy for obesity prevention, but many trials have found non-significant effects on body mass index (BMI). We examined the impact of school PE on adiposity in adolescents, using an ecological analysis to relate the number of PE sessions to changes in BMI and waist circumference. Research methods and procedures: Five-year, longitudinal, school-based study involving 34 secondary schools in London, England. Students were aged 11-12 years at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Boys between 11 and 12 years of age who participated in physical education classes three times a week decreased their waist circumference by about 3 cm when compared to boys who participated only once or twice. The comparisons between girls showed the same behaviour, but without a statistically significant difference 35 .…”
Section: Discussionmentioning
confidence: 75%
“…Boys between 11 and 12 years of age who participated in physical education classes three times a week decreased their waist circumference by about 3 cm when compared to boys who participated only once or twice. The comparisons between girls showed the same behaviour, but without a statistically significant difference 35 .…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have shown that PA accrued in PE settings is associated with improved health outcomes in children and adolescents weight status (Datar & Sturm, 2004;Sollerhed & Ejlertsson, 2008;Wardle, Brodersen & Boniface, 2007) bone health (Weeks, Young & Beck, 2008) and blood pressure (Mc Murray et al, 2002). Some evidence also indicates that engagement in PE during childhood is associated with long-term positive effects on PA level, attitudes toward PA, and perceptions of barriers to PA during adulthood.…”
Section: Physical Activity In Physical Educationmentioning
confidence: 99%
“…The number of PE classes did not have a significant influence on changes in mean students' BMIs for both boys and girls. The authors noted that the nonsignificant influence of higher number of PE classes on mean BMIs could be due to the increase of muscle mass from the result of exercise (Wardle, Brodersen, & Boniface, 2007). classroom curriculum, parent education, and health risk examination.…”
Section: Programs Implemented In School Settingsmentioning
confidence: 99%